The Determinants of Market Participation and Its Effect on Food Security of the Rural Smallholder Farmers in Limpopo and Mpumalanga Provinces, South Africa - Hlatshwayo, Simphiwe Innocentia (Agriculture (Basel), 2022)
Addressing the disproportionate burden of food insecurity in South Africa requires targeted efforts to help smallholder farmers to access markets. The purpose of this study was to assess determinants of market participation and its contribution to household food security. The secondary data used in this study were collected from 1520 respondents; however, 389 smallholder farmers participated in the market. The Household Food Insecurity Access Scale revealed that out of the total sample size, 85% of the households were food insecure while 15% were food secure. Gender of household head, receiving social grants and higher wealth index positively impacted market participation. Having a family member with HIV had a negative impact on market participation among smallholder farmers. The results from the extended ordered probit regression model showed that household size, having a family member with HIV and agricultural assistance had a positive and significant contribution to the household food insecurity situation of the smallholder farmers. On the other hand, the educational level of household head, ownership of livestock, age of household head, gender of household head, and having access to social grants had a negative and significant effect on the food insecurity status. Access to education and the market can improve household food security. Linking smallholder farmers, particularly women and aged farmers, to markets should form an intrinsic part of the government’s efforts to improve farming and food security and increase access to diversified food.